Physical And Sensory Test Of Ice Cream With The Addition Of Sago Flour And Coconut Dregs Flour - Veron Orlando Tamauka; Lucia Cecilia Mandey; Christine Fransin Mamuaja (Jurnal Agroekoteknologi Terapan, 2022)
Ice cream is a processed food product with a semi-solid texture that can be easily modified. Sago flour and coconut dregs flour as an alternative to local food that can be added to ice cream. This study aims to produce ice cream with good quality standards with preferred sensory properties. This study used a completely randomized design (CRD). The results of the research on overrun ice cream with the addition of sago flour and coconut dregs flour obtained an average value between 13-41.6%, melting power obtained an average value ranging from 17.3-31.3 minutes, sensory testing of preference level (color, texture, aroma, taste) obtained an average value of 3.32-3.8 (color), 2.92-3.44 (texture), 2.88-3.28 (aroma) and 1.76-3, 92 (flavor). Based on the results of the study, the addition of sago flour and pulp flour had the highest melting power in the 5% addition treatment, the highest overrun value was in the 0% control treatment and from the panelists' preference for ice cream, the addition of sag flour and coconut dregs flour in terms of color, texture, aroma. , flavor.Â Keywords: Ice cream; Sago flour; coconut dregs flour.